2020
DOI: 10.1101/2020.02.11.944801
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual and semantic representations predict subsequent memory in perceptual and conceptual memory tests

Abstract: Acknowledgments:The authors would like to thank Aude Oliva and Wilma Bainbridge for help in the conception of this project, and Alex Clarke for helpful comments on the manuscript. AbstractIt is generally assumed that the encoding of a single event generates multiple memory representations, which contribute differently to subsequent episodic memory. We used fMRI and representational similarity analysis (RSA) to examine how visual and semantic representations predicted subsequent memory for single item encoding … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 82 publications
0
12
0
Order By: Relevance
“…Corroborating the role of semantic processing in effective encoding, existing studies have shown that the semantic similarity among the study materials predicts later long-term memory ( 55 , 56 ), and a semantic encoding task ( 57 ) and semantical elaboration ( 58 ) could facilitate memory encoding. Nevertheless, our data cannot exclude the possibility that the visual representations in primary visual cortex could contribute to subsequent memory, particularly when a perceptual memory test was used ( 59 ).…”
Section: Discussionmentioning
confidence: 88%
“…Corroborating the role of semantic processing in effective encoding, existing studies have shown that the semantic similarity among the study materials predicts later long-term memory ( 55 , 56 ), and a semantic encoding task ( 57 ) and semantical elaboration ( 58 ) could facilitate memory encoding. Nevertheless, our data cannot exclude the possibility that the visual representations in primary visual cortex could contribute to subsequent memory, particularly when a perceptual memory test was used ( 59 ).…”
Section: Discussionmentioning
confidence: 88%
“…4) We computed the correlation between the dissimilarity of each object with the rest of the objects in terms of stimulus properties (each row of the model RDM) and the dissimilarity of the same object with the rest of the objects in terms of activation patterns (each row of the brain RDM) and identified brain regions that demonstrated a significant correlation across all items and subjects. Davis et al (2021) termed the strength of this second-order correlation as the item-wise RDM-activity fit (IRAF). The IRAF in a brain region is therefore an index of the sensitivity of that region to that particular kind of visual or semantic representation.…”
Section: Multivariate Fmri Analysismentioning
confidence: 99%
“…Whereas the notion of a cortical posterior-anterior gradient from perception to memory is well supported, the question whether the magnitude of the retrieval-related anterior shift impacts memory performance has been largely unexplored (but see Davis et al, 2021). Here, we sought for relationships between the anterior shift and memory performance on the assumption that memory for the details of an event is more likely to be accurate when there is strong overlap (indexed by a relatively small anterior shift) between experienced and retrieved event representations (see Introduction).…”
Section: Discussionmentioning
confidence: 99%